ALS-linked KIF5A ΔExon27 mutant causes neuronal toxicity through gain-of-function - Pant, Devesh C.; Parameswaran, Janani; Rao, Lu; Loss, Isabel; Chilukuri, Ganesh; Parlato, Rosanna; Shi, Liang; Glass, Jonathan D; Bassell, Gary J; Koch, Philipp; Yılmaz, Rüstem; Weishaupt, Jochen H.; et al. (EMBO reports, 2022)
Abstract Mutations in the human kinesin family member 5A (KIF5A) gene were recently identified as a genetic cause of amyotrophic lateral sclerosis (ALS). Several KIF5A ALS variants cause exon 27 skipping and are predicted to produce motor proteins with an altered C-terminal tail (referred to as ?Exon27). However, the underlying pathogenic mechanism is still unknown. Here, we confirm the expression of KIF5A mutant proteins in patient iPSC-derived motor neurons. We perform a comprehensive analysis of ?Exon27 at the single-molecule, cellular, and organism levels. Our results show that ?Exon27 is prone to form cytoplasmic aggregates and is neurotoxic. The mutation relieves motor autoinhibition and increases motor self-association, leading to drastically enhanced processivity on microtubules. Finally, ectopic expression of ?Exon27 in Drosophila melanogaster causes wing defects, motor impairment, paralysis, and premature death. Our results suggest gain-of-function as an underlying disease mechanism in KIF5A-associated ALS.